Analisis Tingkat Technopreneurship Pada UMKM Sambel Pecel Wahyu Tumurun Kota Madiun - Ramadhan, Dyan, Suci (Universitas PGRI Madiun, 2018)
Madiun city is one of the cities located in the East Java region that has a typical foodthat is